English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

It is not my homework , i am just trying to check my answer , if i got corect or not .

Thanks Friends

2006-11-12 07:01:58 · 6 answers · asked by Asker 1 in Science & Mathematics Mathematics

6 answers

Hi again

Y = √2x – 3
2x – 3 = y ²
X =( y ² + 3 )/ 2
f –¹ (x) =( y ² + 3 )/ 2 => f –¹ (x) = (x ² + 3 )/ 2 & x ≥ 0

Good Luck
try to solve them yourslef again if you got wrong , am sure you can solve them correctly , if you just try your best

2006-11-12 07:03:30 · answer #1 · answered by sweetie 5 · 6 0

Your question is somewhat ambiguous.
Is it √2 x - 3, √(2x) - 3, or √(2x-3) ?
As written, using standard rules, the first is the function.
If so,
y = √2 x - 3
in the inverse,
x = √2 y - 3
x+3 = √2 y
y = (x+3)/√2 = √2(x+3)/2

2006-11-12 15:09:01 · answer #2 · answered by ʎɓʎzʎs 3 · 0 1

If I understand you question correctly -
Given:
f(x) = √(2x) – 3 , find the first derivative of x.
f(x) = (2x)^½ – 3
f `(x) = (½)(2x)^-½ – 0
f `(x) = 1/2(2x)^½
f `(x) = 1/ 2√2x

2006-11-12 16:01:02 · answer #3 · answered by Brenmore 5 · 0 1

(2x-3)to the power 0.5
=0.5(2x-3)to the power 0.5 multiply by2
=(2x-3)to the power 0.5
i had this lesson today in calculus

2006-11-12 15:17:42 · answer #4 · answered by nano_1992_fun 2 · 0 0

x2 + 3 divided by 2


i think.

2006-11-12 15:06:42 · answer #5 · answered by MsPacman 2 · 0 0

if y = (sqrt(2))x - 3,
x = (1/sqrt(2))(y+3)
so f^-1(x) = (1/sqrt(2))(x+3)




if y =(sqrt(2x))-3
x = ((y+3)^2)/2
so f^-1(x) = ((x+3)^2)/2

if y = sqrt(2x-3)
x= (y^2+3)/2
so f^-1(x) = (x^2+3)/2

2006-11-12 15:14:55 · answer #6 · answered by paladin 1 · 1 0

fedest.com, questions and answers